Betta nuluhon, a new species of fighting fish from western Sabah, Malaysia (Teleostei: Osphronemidae) - Kamal, N. S. S.; Tan, H. H.; Ng, Casey K. C. (Zootaxa, 2020)
Betta nuluhon, new species, is described from a hill stream habitat in western Sabah. This species is allied to both B. chini and B. balunga, and differs from rest of its congeners in the B. akarensis group in having the following combination of characters: yellow iris when live; mature males with greenish-blue iridescence on opercle when live; mature fish with distinct transverse bars on caudal fin; slender body (body depth 22.1–25.2 % SL); belly area with faint reticulate pattern (scales posteriorly rimmed with black); absence of tiny black spots on anal fin; lateral scales 29–31 (mode 30); predorsal scales 20–21 (mode 20). Notes on a fresh series of B. chini are also provided.